Students’ perceptions regarding problem-based learning in community medicine - Johnson, Liaquat R.; Nair, Narayanan S.; Simon, Catherine; Binu, Jeffy (International Journal Of Community Medicine And Public Health, 2018)
Background: Although a problem based learning (PBL) program in community medicine was introduced over a year ago, student perceptions about the same had not been elicited. This study was conducted to ascertain the perceptions regarding the PBL program from a representative sample of students completing the same. Methods: This cross-sectional study was conducted among 32 semester 7 medical students in a private medical college in south India. Data were collected anonymously after obtaining written informed consent. Students rated their own involvement in the PBL program; confidence across broad PBL areas before and after the program; usefulness of the broad PBL areas; and how likely they were to use the broad PBL areas, using a 10-point rating scale. Statistical analyses were performed using EZR (version 1.36). Descriptive statistics, Mann-Whitney U test, Wilcoxon signed-rank test, Cronbach’s alpha were employed. Results: Of the participants, 20(62.5%) were female. There was a statistically significant difference in perceived confidence across all broad PBL areas following the program, compared to ratings before the program. The median overall rating for the program was 8/10. Greater student involvement was significantly associated with higher ratings for confidence following the program; usefulness in most broad PBL areas. Male gender was significantly associated with high ratings in some broad PBL areas. Conclusions: A PBL approach can improve student perceptions of confidence in generic skills. High student involvement is key to good student perceptions regarding a PBL program.